Evaluation Residual Moisture in Lithium-Ion Battery Electrodes and Its Effect on Electrode Performance. Issue 15 (2016) - Li, Jianlin; Daniel, Claus; An, Seong Jin; Wood, David
ABSTRACT: Removing residual moisture in lithium-ion battery electrodes is essential for desired electrochemical performance. In this manuscript, the residual moisture in LiNi0.5 Mn0.3 Co0.2 O2 cathodes produced by conventional solvent-based and aqueous processing is characterized and compared. The electrochemical performance has also been investigated for various residual moisture contents. It has been demonstrated that the residual moisture lowers the first cycle coulombic efficiency, but its effect on short term cycle life is insignificant.